Salvation and Free Will in Bramantino. Figures and Gestures in the Brera Crucifixion (Studi di storia medioevale e di diplomatica - Nuova Serie, 2024)
The article proposes an iconological re-reading of one of Bramantino's most controversial works, the Brera Crucifixion. By analysing hitherto neglected gestures and figures, the essay reveals the painter's ultimate aim: to depict human freedom in the face of the Saviour's offer of grace. In the light of this highly original iconography, the article then explores the possible contexts of production and identifies the condemnation of the Lutheran theses sanctioned by the Exsurge Domine (1520) as a probable source of inspiration.
Keywords: Bramantino; Luther; Free Will; Exsurge Domine; Duchy of Milan; Sforza